Mass communications - West, Douglas (Henry Stewart Talks, 2012)
Definition and scope of mass media, Key trends, Mass media strategy, Types of media, Web, Press, TV, Radio, Billboards, Cinema, Synergies between media
Archived at 2022/04/26